2018
DOI: 10.1038/s41419-018-0939-5
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant milk fat globule-EGF factor-8 reduces apoptosis via integrin β3/FAK/PI3K/AKT signaling pathway in rats after traumatic brain injury

Abstract: Accumulating evidence suggests neuronal apoptosis has the potential to lead to more harmful effects in the pathological processes following traumatic brain injury (TBI). Previous studies have established that milk fat globule-EGF factor-8 (MFG-E8) provides neuroprotection through modulation of inflammation, oxidative stress, and especially apoptosis in cerebral ischemia and neurodegenerative disease. However, the effects of MFG-E8 on neuronal apoptosis in TBI have not yet been investigated. Therefore, we explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…Activation of the signaling pathway can inhibit a variety of stimulationinduced apoptosis mechanisms and promote cell cycle progression, thereby promoting cell survival and proliferation while participating in angiogenesis 14 . The current study found that activation of the PI3K/AKT pathway can signi cantly reduce the area of brain damage and the rate of apoptosis 15 . Activated AKT can also protect rat hippocampal neurons and cortical neurons against hypoxia/reoxygenation-induced apoptosis [16][17][18] . In this study, we hypothesized that PF + CG may confer protection from brain damage following cerebral ischemia via the PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the signaling pathway can inhibit a variety of stimulationinduced apoptosis mechanisms and promote cell cycle progression, thereby promoting cell survival and proliferation while participating in angiogenesis 14 . The current study found that activation of the PI3K/AKT pathway can signi cantly reduce the area of brain damage and the rate of apoptosis 15 . Activated AKT can also protect rat hippocampal neurons and cortical neurons against hypoxia/reoxygenation-induced apoptosis [16][17][18] . In this study, we hypothesized that PF + CG may confer protection from brain damage following cerebral ischemia via the PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the therapeutic effects of Lactadherin in stroke (23,24,26,52). Lactadherin exerts neuroprotection against cerebral injury by suppressing inflammation, reducing neuronal cell death, promoting apoptotic cell clearance (26). Additionally, Lactadherin improves subarachnoid hemorrhage (SAH) outcome via anti-oxidation which may be dependent on integrin β3/ nuclear factor erythroid 2-related factor 2/HO pathway (24).…”
Section: Discussionmentioning
confidence: 97%
“…Lactadherin mediates cell-cell interactions and is involved in various physiological and pathophysiological functions including angiogenesis (49), fertilization (50), inflammation (23) and clearance of apoptotic cells (51). Several studies have confirmed the therapeutic effects of Lactadherin in stroke (23,24,26,52). Lactadherin exerts neuroprotection against cerebral injury by suppressing inflammation, reducing neuronal cell death, promoting apoptotic cell clearance (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of MFG-E8 could alleviate pathological lesion of Alzheimer's disease (AD) via modulating the alteration of M1/M2 polarization [14]. Recently our laboratory have confirmed that recombinant human MFG-E8 (rhMFG-E8) improve neurological function in an animal model of traumatic brain injury (TBI) by inhibiting neuronal apoptosis [17]. These studies indicated that MFG-E8 could provide neuroprotection in CNS.…”
Section: Introductionmentioning
confidence: 96%